2020
DOI: 10.3390/met10070938
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tribological Properties in Disks of AA-5754 and AA-5083 Aluminium Alloys Previously Processed by Equal Channel Angular Pressing and Isothermally Forged

Abstract: In the present study, the wear behaviour of two aluminium alloys (AA-5754 and AA-5083) is analysed where these have been previously processed by severe plastic deformation (SPD) with equal channel angular pressing (ECAP). In order to achieve the objectives of this study, several disks made of these alloys are manufactured by isothermal forging from different initial states. The microstructures of the initial materials analysed in this study have different accumulated deformation levels. In order to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…According to the results of computer simulation, it was found that the temperature and strain rate in the studied range of parameters do not have a noticeable effect on strain distribution during the ECAP of zinc alloy ( Figure 4 ). This corresponds to the opinion that strain distribution during ECAP is determined mainly by the geometry of the channels, the angle of their intersection, tribological conditions and the strain capacity [ 14 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 83%
“…According to the results of computer simulation, it was found that the temperature and strain rate in the studied range of parameters do not have a noticeable effect on strain distribution during the ECAP of zinc alloy ( Figure 4 ). This corresponds to the opinion that strain distribution during ECAP is determined mainly by the geometry of the channels, the angle of their intersection, tribological conditions and the strain capacity [ 14 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 83%
“…The first simulation employs a friction coefficient of 0.3, which represents the friction between two steels lubricated with standard cutting oil and is considered representative of the actual process. This value was used in other works [27,28]. Subsequently, a second simulation is conducted with a friction coefficient of 0.1, with the assumption that this modification will result in lower stress levels on both dies.…”
Section: Geometrymentioning
confidence: 99%
“…They identified two major types of wear relevant to industrial applications of Al–Si alloys: sliding wear and abrasive wear depending on the silicon particles, intermetallic constituents, and matrix hardness. Luis Pérez et al [ 37 ] studied the friction properties of AW-5083 and AW-5754 aluminium alloys processed by equal channel angular pressing (ECAP). It was found that both nanostructured aluminium alloys show better wear behaviour if they are compared with conventional isothermal forging.…”
Section: Introductionmentioning
confidence: 99%